Effect of Dehydration Method on Quality of Longan Honey - Jaturonglumlert, Somkiat; Suriwong, Voraluck; Thaisamak , Phirunrat; Kaewdam, Sakawduan (Burapha Science Journal, 2026)
This research aimed to study the effect of moisture dehydration on physicochemical properties of longan honey and try to explain the dehydration mechanism of longan honey by mathematical model. The results showed that the dehydration with vacuum - infrared drying at temperatures of 30, 40, 50 and 60°C removed the moisture content in by 33.33 – 42.31%. On the other hand, moisture content of honey was removed by 7.69 - 17.95% using the hot air drying with drying time up to 6 hours, more than dehydration with a vacuum - infrared drying up to 36 times. At 40°C, 20 mins dehydration with vacuum – infrared drying provided color (L*, a*, b*) and water activity (aw) not significantly different from honey sample before moisture dehydration (p<0.05) and could adjust glucose/water ratio in raw material preparation for creamed honey production. The R2 values indicates the Newton’s and Page’s models fit reasonably well with the experimental data, so it was to be a good model for describing the moisture reduction in longan honey with both method at 40°C. However, the conditions of dehydration in each type of honey differ, it depends on the physical and chemical properties of honey.